Penanganan Multidisiplin Tuberkulosis Paru Multi-Drug Resistant Diseminata dengan Spondilitis Tuberkulosis Thorakolumbal dan Komplikasi Paraparesis Berat - Budi Jefri (Majalah Ilmiah METHODA, 2025)
Background: Multidrug-resistant (MDR) tuberculosis (TB) is a global challenge. Tuberculous spondylitis (Pott's disease) is the most devastating extrapulmonary manifestation. Cases of MDR pulmonary TB with vertebral involvement and severe neurological complications require aggressive and coordinated management. Case Presentation: We report the case of Mr. RP, a 22-year-old man diagnosed with MDR pulmonary TB and MDR tuberculous spondylitis of the thoracic-lumbar spine (Th3-Th4). The patient presented with progressive upper motor neuron (UMN) paraparesis (motor 2/5), back pain (since 7 months), hypoesthesia around Th5-6, and autonomic dysfunction (urinary/defecatory disorders). The diagnosis of MDR TB was confirmed by TCM sputum (MTB detected, Rif Res) and confirmed by Rif Res findings in cerebrospinal fluid (CSF). Thoracolumbar MRI showed compression and destruction of Th3-Th4 vertebral bodies, kyphotic alignment, paravertebral masses, and Th3 spinal cord edema. The patient also had subclinical hypothyroidism and hyperuricemia. Management: The patient was given a long-term treatment plan for MDR-TB that included Bedaquiline, Levofloxacin, Line One week after initiation of anti-TB treatment, a decompressive laminectomy, posterior fusion, and biopsy were performed on November 7, 2024. Results: At the 6-month follow-up (April 28, 2025), the patient demonstrated dramatic neurological improvement, able to walk independently with full muscle strength (Motor 5/5) in all extremities. Conclusion: This case underscores the importance of early diagnosis of disseminated MDR-TB and the success of a combined therapeutic approach, namely immediate surgical decompression followed by aggressive and appropriate MDR-TB therapy, in achieving optimal functional recovery.